Reduced gray matter volume in normal adults with a maternal family history of Alzheimer disease - Honea, R A. (American Academy of Neurology, 2010)
OBJECTIVE: A consistently identified risk factor for Alzheimer disease (AD) is family history of dementia, with maternal transmission significantly more frequent than paternal transmission. A history of maternal AD may be related to AD-like glucose consumption in cognitively healthy subjects. In this cross-sectional study, we tested whether cognitively healthy people with a family history of AD have less gray matter volume (GMV), an endophenotype for late-onset AD, than individuals with no family history, and whether decreases in GMV are different in subjects with a maternal family history. METHODS: As part of the Kansas University Brain Aging Project, 67 cognitively intact individuals with a maternal history of late-onset AD (FHm, n = 16), a paternal history of AD (FHp, n = 8), or no parental history of AD (FH−, n = 43), similar in age, gender, education, and Mini-Mental State Examination score, were scanned at 3 T. We used voxel-based morphometry to examine GMV differences between groups, controlling for age, gender, and apoE4. RESULTS: Cognitively healthy individuals with a family history of late-onset AD had significantly decreased GMV in the precuneus, middle frontal, inferior frontal, and superior frontal gyri compared with FH− individuals. FHm subjects had significantly smaller inferior frontal, middle frontal, precuneus, and lingual gyri compared with FH− and FHp subjects. CONCLUSIONS: Overall, maternal family history of Alzheimer disease (AD) in cognitively normal individuals is associated with lower gray matter volume in AD-vulnerable brain regions. These data complement and extend reports of cerebral metabolic differences in subjects with a maternal family history. GLOSSARY: AD: = Alzheimer disease; BA: = Brodmann area; CDR: = Clinical Dementia Rating; FH+: = parental family history of Alzheimer disease; FH−: = no family history of Alzheimer disease; FHm: = maternal family history of Alzheimer disease; FHp: = paternal family history of Alzheimer disease; GMV: = gray matter volume; mtDNA: = mitochondrial DNA; TICV: = total intracranial volume.